Maternal and Child Clinic, Dental School, University of Passo Fundo (UPF): patient profile - Larissa Corrêa Brusco PAVINATO; Juliane BERVIAN; Eduardo Grigollo PATUSSI; Moisés CARDOSO; Gabriela dos Santos PINTO (Faculdade São Leopoldo Mandic, 2018)
Objective: Characterizing the profile of patients seen at the Maternal and Child Clinic from the University of Passo Fundo Dental School. Methods: 694 records were evaluated in the years 2000 to 2011. Demographic (gender, age and place of residency), clinical and therapeutic variables (previous dental experience, caries, reason for dental appointment, procedures performed, number of appointments and completion of treatment) were collected for descriptive statistical analysis and associations. Results: There was a higher demand for treatment from male children (51.4%) aged 25 to 36 months (61.4%), being 86% of patients from Passo Fundo, Rio Grande do Sul. It was also found that 51% of patients had caries and the main reason for dental appointment was treating such lesion (43.2%). Among the most commonly performed procedures, the non-invasive treatments (49.4%) were the ones that occurred more frequently. Regarding the studied variables, there was an association between children aged 25 - 36 months, living in Passo Fundo, and caries treatment. Conclusion: The evaluated and associated data allowed the definition of the profile of patients seen at the Maternal and Child Clinic. The great majority of patients were male subjects aged 25 -36 months, from Passo Fundo, and who had not undergone previous dental treatment, being caries the major reason for appointment. This study traces the profile of patients and reinforces the need for early preventive treatment and proposals for this age group, aiming at decreasing the need for treatment and reducing diseases in children.